(untitled) (Conference on English Language Teaching, 2024)
This study explores the impact of using K-pop as an English learning and teaching tool among Indonesian students. The focus of this study includes how English skills are improved through Kpop, how Kpop affects interest in learning, and how social media impacts interest and ability to learn English. This study used a quantitative method by giving questionnaires to six K-pop fan students. The results show that the use of KPop as a learning tool provides significant results in improving students’ English skills. Moreover, K-Pop can be considered as an effective tool to assist students in improving skills based on their interest in learning the language. This study provides insight into the potential use of other media that match students’ interests to improve the effectiveness of English language learning in Indonesia.